"Like Yin and Yang": Perceptions of Methamphetamine Benefits and Consequences Among People Who Use Opioids in Rural Communities. Issue 1 (January 2021) - Baker, Robin; Leichtling, Gillian; Hildebran, Christi; Pinela, Cristi; Waddell, Elizabeth Needham; Sidlow, Claire; Leahy, Judith M.; Korthuis, P. Todd
Abstract : Objectives: The objective of this study was to investigate methamphetamine use among people who use opioids in rural Oregon communities to explore reasons for use and perceptions of methamphetamine consequences. Methods: We conducted interviews and surveys with participants who inject drugs or misuse prescription opioids in 2 rural Oregon counties with high opioid overdose rates. Survey participants were identified through participant-driven sampling initiated in syringe service programs and field outreach (n = 144). Semi-structured interviews with participants were recruited from the same locations (n = 52). Results: Of 144 surveys completed, 112 reported using opioids in the past 30 days; 96% of the 112 also report methamphetamine use. Among the 124 reporting injection drug use, 50% indicated they injected both methamphetamine and heroin in the past 30 days. Interview participants reported early exposure to methamphetamine and indicated that methamphetamine was more widely available, less expensive, and less stigmatized compared to heroin. Participants reported using methamphetamine to improve work-life functioning and because they enjoy the high produced from simultaneous use. Several participants reported a conscious effort to shift to methamphetamine from heroin as a harm reduction strategy. Some participants reported being involuntarily discharged from treatment for opioid use disorder due to methamphetamine use. Several participants perceived methamphetamine as conveying overdose prevention or reversal benefits, while fentanyl contamination in methamphetamine was reported or suspected. Conclusion: As rural communities respond to evolving drug supply and demand, there is increasing need for public health efforts to address the emerging issue of concurrent methamphetamine and opioid use.